(3HdhZ GdCQH aj eYQaI UfGYI GdaVI hGdPgHs - (3GddYjHj, CHh LYaQ, eMeO Hf QVGs
(3ChdgG (B:s
(3GdMeO ddg SGHZ GdfYe(B... (3hHYO(B... (3deG QCjJ Yde GdcjejGA YdeG jWdHg CcKQ GdfGSs
(3BNQgG (B:s
(3heG PcQJ ef GdSDGd hGdLhGH aj bhdg Yf MbjbI GdCcSjQ GdCMeQ GdeJNP ef GdcHQjJ GdCUaQ(B... (3dCfj dG CYjOg KGfjGs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdUfGYI hGdCWYeIs